Body mass index, neck circumference, and hypertension: a prospective cohort study - Ren, Tao-jun; Zhang, Kun; Li, Wen-juan; Ren, Shu-tang; Huang, Yun-zhou; Yang, Ning; Wu, Shou-ling; Li, Yu-ming (Frontiers in Cardiovascular Medicine, 2023)
Objective This study aimed to investigate the association between BMI combined with neck circumference and the risk of hypertension. Methods We selected participants from the Kailuan study in 2014 who were normotensive as our research subjects. We compared the risk of hypertension among individuals in group 1 (non-obese with low neck circumference), group 2 (non-obese with high neck circumference), group 3 (obese with low neck circumference), and group 4 (obese with high neck circumference). Results After a median observation period of 3.86 years, hypertension occurred in 13,383 participants. Subjects in Group 2, 3, and 4 had significantly higher risks of hypertension compared to Group 1, with hazard ratios (HRs) of 1.066 (95% CI: 1.025, 1.110), 1.322 (95% CI: 1.235, 1.415), and 1.422 (95% CI: 1.337, 1.512), respectively. Additionally, adding BMI to a conventional model had a greater incremental effect on predicting hypertension compared to adding neck circumference alone. However, considering both BMI and neck circumference together further improved the prediction of hypertension. Conclusion Individuals with both high BMI and high neck circumference face a higher risk of hypertension. Moreover, BMI is a superior predictor of hypertension risk compared to neck circumference, but using both of these measures can further enhance the accuracy of hypertension risk prediction.